2010
DOI: 10.3810/pgm.2010.01.2107
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Diagnosis and Treatment of Rosacea

Abstract: Rosacea is a common chronic inflammatory disease of the skin and is associated with a number of etiological causes and inciting factors. It is characterized by erythematous changes of the facial skin, and commonly presents with papules, pustules, or telangiectasias. The 4 subtypes of rosacea are categorized according to secondary symptoms, such as pain, erythema, dryness, and edema. A number of therapies are available to treat rosacea, some of which can be used in combination. The mainstays of therapy are topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 38 publications
0
32
0
4
Order By: Relevance
“…The natural history of rosacea is unknown and progression within and between subtypes has been implied. [25][26][27][28] In this study, progression between subtypes was addressed by surveying subjects with rosacea about the order of appearance of rosacea-associated signs and symptoms by retrospective recall. We found that, despite a prolonged duration of rosacea with a mean of 21 years (median 20 years), the majority of subjects with ETR (69%) did not fulfil the criteria for PPR.…”
Section: Discussionmentioning
confidence: 99%
“…The natural history of rosacea is unknown and progression within and between subtypes has been implied. [25][26][27][28] In this study, progression between subtypes was addressed by surveying subjects with rosacea about the order of appearance of rosacea-associated signs and symptoms by retrospective recall. We found that, despite a prolonged duration of rosacea with a mean of 21 years (median 20 years), the majority of subjects with ETR (69%) did not fulfil the criteria for PPR.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies do not agree on the exact target/binding site of the tetracyclines on the 16S rRNA (12). In addition, there is increasing evidence of other useful properties of the tetracyclines, such as their antiviral (2,13,14), anti-inflammatory (4,15), antiapoptotic (2), and neuroprotective activities (1), that are not explained by the 16S rRNA binding mechanism currently held for the antibacterial action of the tetracyclines.…”
mentioning
confidence: 96%
“…Therefore, it is essential to be aware of the presence of rosacea to appropriately treat ocular surface disease that is not responding as expected to topical therapy 6 10 11. Indeed, our patient, who had previously received several topical treatments with a poor response, improved with a 2-month course of oral doxycycline.…”
Section: Discussionmentioning
confidence: 89%